Effect of methotrexate/vitamin B12 on DNA methylation as a potential factor in leukemia treatment-related neurotoxicity. (September 2017) - Forster, Victoria J; McDonnell, Alex; Theobald, Rachel; McKay, Jill A
Methotrexate (MTX) is administered to treat childhood acute lymphoblastic leukemia (ALL). It acts by inhibiting dihydrofolate reductase which reduces methyltetrahydrofolate, a key component in one carbon metabolism, thus reducing cell proliferation. Further perturbations to one carbon metabolism, such as reduced vitamin B12 levels via the use of nitrous oxide for sedation during childhood ALL treatment, may increase neurotoxicity risk. With B12 as an enzymatic cofactor, methyltetrahydrofolate is essential to produce methionine, which is critical for DNA methylation. We investigated global and gene specific DNA methylation in neuronal cell lines in response to MTX treatment and vitamin B12 concentration individually, and in combination.Results: MTX treatment alone significantly increased LINE-1 methylation in SH-SY5Y (p = 0.040) and DAOY (p < 0.001), and increased FKBP5 methylation in MO3.13 cells (p = 0.009).Conclusion: We conclude that altered DNA methylation of brain/central nervous system cells could be one mechanism involved in MTX treatment-related neurotoxicities and neurocognitive late effects in ALL survivors.